2016
DOI: 10.1108/md-02-2016-0117
|View full text |Cite
|
Sign up to set email alerts
|

The influences of knowledge loss and knowledge retention mechanisms on the absorptive capacity and performance of a MIS department

Abstract: Purpose – Knowledge loss impact on the performance of management information system (MIS) departments due to its influence on absorptive capacity. Furthermore, knowledge retention in human resource management and information system application is also included in the research model, in order to examine their effectiveness in mitigating knowledge loss. The paper aims to discuss these issues. Design/methodology/approach – Survey method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 55 publications
2
82
0
4
Order By: Relevance
“…Mariano and Walter (2015) suggest that empirical researches on the absorptive capacity in the fields of knowledge management and intellectual capital should be directed to explore and explain contributions of intellectual capital factors to organizational dynamic processes. The study by T.-C. Lin, Chang and Tsai (2016) explored the relationship between the loss of knowledge and decrease of absorptive capacity, providing empirical evidence on impacts of the loss of knowledge including in performance decrease. BAR, Rio de Janeiro, v. 13, n. 4, art.…”
Section: Absorptive Capacity (Ac): a Challenge In Organizational Manamentioning
confidence: 99%
“…Mariano and Walter (2015) suggest that empirical researches on the absorptive capacity in the fields of knowledge management and intellectual capital should be directed to explore and explain contributions of intellectual capital factors to organizational dynamic processes. The study by T.-C. Lin, Chang and Tsai (2016) explored the relationship between the loss of knowledge and decrease of absorptive capacity, providing empirical evidence on impacts of the loss of knowledge including in performance decrease. BAR, Rio de Janeiro, v. 13, n. 4, art.…”
Section: Absorptive Capacity (Ac): a Challenge In Organizational Manamentioning
confidence: 99%
“…In simpler words, it can be described as a conversation between the organization's representative and the resigning employee that not only identifies the employee's reasons for leaving but also provides information that helps improve the organization's performance (Ton & Huckman, ). Thus, the exit interview can be used to help the organization reduce turnover (Lin, Chang, & Tsai, ). It can also provide insight into such areas as compensation and benefit policies, training and development programs, career development roadmaps, pension programs, and any programs that could use improvement (Williamson & Harris, ).…”
Section: The Essence Of Employee Retentionmentioning
confidence: 99%
“…Despite general remarks why knowledge protection is important, not much is published about real consequences of the realization of knowledge risks. For the risk of losing knowledge inside the company, e.g., due to employee retirement, studies try to quantify the impact of knowledge loss and suggest that knowledge loss causes organizational problems like low productivity or reduced moral [31], others investigate the relationship between knowledge loss and performance [25] or the skills of responsible staff [19]. Also for risk of losing reputation some studies can be found [e.g.…”
Section: Introductionmentioning
confidence: 99%